Biological responses of ultrafine grained pure titanium and their sand blasted surfaces - Günay Bulutsuz, Aslı; Berrak, Özge; Yeprem, H. Aygül; Yurci, Mehmet Emin; ARISAN, ELİF DAMLA (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2018)
The use of materials as implants has become vital for determining optimal product design to enhance the needs of usage and longevity in body. Ultrafine grained pure titanium offers advanced mechanical properties for medical applications for most adequate materials meso/micro scaled dental implants. Besides advanced mechanical properties, increased surface properties also offers enhance biocompatibility. In this experimental study, the effects of bulk structure on surface modification by sand blasting for coarse-grained and ultrafine-grained (UFG) commercially pure titanium reported. To determine the effects of bulk structure on the polished and modified surfaces the specimen groups are investigated using Optic Microscope (OM), Electron Back Scattering Diffraction (EBSD) and Confocal Laser-Scanning Microscope (CLSM). Surface roughness is determined with stylus profilometer (SP) and CLSM. Understanding the biocompatibility of titanium surfaces to cell-cell interactions and cell proliferation capacity of attached-cells were determined by cell viability assays and fluorescence microscopy techniques. According to our results, the titanium surfaces were highly available to cell attachment and cell proliferation. The ratios of cell proliferation of cells which are attached on different titanium surfaces were dependent on the grain size and the surface roughness. UFG and blasted surfaces are more suitable for cell proliferation of human gingival fibroblast cells.
Keywords: Titanium; Dental Implants; Biocompatibility; Ultrafine-grained; Cell culture; SEVERE PLASTIC-DEFORMATION; HIGH-PRESSURE TORSION; IN-VITRO BIOCOMPATIBILITY; MECHANICAL-PROPERTIES; NANOSTRUCTURED TITANIUM; BIOMEDICAL APPLICATIONS; IMPLANT SURFACES; DENTAL IMPLANTS; ROUGHNESS; ALLOY; Titanium; Dental İmplants; Biocompatibility; Ultrafine-grained; Cell culture